Pengaruh Penambahan Tepung Temulawak (Curcuma xanthoriza) dalam Ransum Terhadap Efisiensi Pakan Sapi Peranakan Simmental - Novi Eka Wati; M. Yusuf (Wahana Peternakan, 2020)
The aim of the study was to know the effect of Curcuma xanthorhiza as herbal feed additive in the rations on dry matter consumption, body weight gain, feed efficiency and feed cost pergain of Simmental cross cattle. The research was conducted at PGS. Joe Cipir Jati Indah Village, Tanjung Bintang District, South Lampung Regency. The experimental used 12 male Simmental Cross Cattle with an average body weight of 166.25 Â± 6.27 kg. The study used a quantitative method with a completely randomized design with 3 treatments and 4 replications. They were fed a complete feeding with control rations + 0% temulawak flour (P0), control ration + 1.5% temulawak flour (P1) and control ration + 3% temulawak flour (P2). The control ration is the usual ration given by farmers every day containing 8.35% crude protein and 59.63% TDN. The study was conducted for 5 weeks, 1 week period of adaptation and 4 weeks period of data collection. The results showed that the addition of temulawak flour had a significant effect (P <0.05) on dry matter consumption, body weight gain, feed efficiency and feed cost per gain of Simmental cross cattle. The 1,5% addition level of temulawak flour from dry matter ration showed the best body weight gain, feed efficiency and feed cost per gain.Keywords:, natural feed additive, production efficiency, Simmental cross cattle , temulawak